PENGARUH WORKED-EXAMPLE MENGGUNAKAN TRACING GESTURE KOGNITIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Ulpah, Maria; Santosa, Cecep Anwar Hadi Firdos; Novaliyosi, Novaliyosi (MES: Journal of Mathematics Education and Science, 2024)
The research aims to determine whether or not there is an influence on mathematical problem solving abilities between students who receive the work-example method using gesture tracing and students who use the work-example method without using gesture tracing. The population in this study was 68 students of SMA Negeri 1 Ciomas for the 2023/2024 academic year and the sample for this research was 68 students of class XI Science-1 and class XI Science-3. This type of research is quantitative research. The data used is the KAM test and the KPMM test with 5 questions. After the screening test is carried out, the data is declared Normal and Homogeneous, then the data can be carried out further tests. The results of data analysis of mathematical problem solving abilities in the work-example learning method using gesture tracing were an average of 74.68 with a standard deviation of 9.905 and in the works-example learning method without using gesture tracing the average was 61.21 with a standard deviation of 9.803. To test the hypothesis, it was concluded that the mathematical problem solving abilities of students who were taught using the works-example learning method using gesture tracing were better than students who were taught using the works-example learning model without using gesture tracing.